The point of it all : a lifetime of great loves and endeavors - Krauthammer, Charles, 1950-2018; Krauthammer, Daniel, 1985- (New York, Crown Forum, 2018)
"Created and compiled by Charles Krauthammer before his death, The Point of It All is an intimate collection of the influential columnist's most important works. Spanning the personal, political and philosophical--including never-before-published speeches and a major new essay about the effect of today's populist movements on the future of global democracy--this is the most profound book yet by the legendary writer and thinker. For longtime readers and newcomers alike, The Point of It All is a timely and much needed demonstration of what it means to cut through the noise of petty politics with clarity, integrity and intellectual fortitude. Edited and with an introduction by the columnist's son, Daniel Krauthammer, the book is a reminder of what made Charles Krauthammer the most celebrated American columnist and political thinker of his generation, a look at the man behind the words, and a lasting testament to his belief that anyone with an open and honest mind can grapple deeply with the most urgent questions in politics and life"--
Part 1. What a piece of work is man. 1: Life well lived. Reveries of a newborn father ; Irving Kristol: a great good man ; Ronald Reagan: he could see for miles ; Thomas Jefferson: the sublime oxymoron ; Thank you, Isaiah Berlin ; John Paul II: the power of faith ; George Weidenfeld: Syrian Christians and the English Jew ; Meg Greenfield: my editor, my friend -- 2: Customs and culture. Why I love Australia ; Rampway to heaven ; Junk rights ; Genius, insanity, innocence ; Two Cromwells: separate and independent realities ; Parenthesis to history ; The Cold War memorials -- 3: Contests. Suffering a relapse, and loving it ; The tyranny of chess ; Revenge, American-style ; Man vs. computer: still a match ; The greatness gap ; Why do they even play the game? ; Jim Dickson's triumph -- 4: Cosmos. In sorrow and glory we find our common humanity ; Front-page physics: why the news from beyond is beyond us ; What Sputnik launched ; Pluto and us ; Space: the visionaries take over ; Redeeming Columbia -- 5: The doctor is in. A doctor's duty ; Why doctors quit ; Sick, tired and not taking it anymore ; The twilight of psychotherapy ; They die with their rights on -- 6: Matters of life and death. Five lives vs. one principle ; Stem cells: mounting the slippery slope ; The abortion debate: just words ; The price of fetal parts ; What to do for little Charlie Gard -- Part 2. Man and society. 7: Look outward. Three pieces of sage advice -- 8: Against the grain. Apocalypse, with and without God ; When modern medicine fails ; The myth of "settled science" ; Thought police on patrol -- 9: The too-examined life. Suicide ad absurdum ; Holiday: living on a return ticket ; Shakespeare, ruined ; Illusions of self-love -- 10: Out of many, one. Assimilation nation ; The tribalization of America ; Counting by race ; Redskins and reason ; Neither ennobling nor degrading ; On lowering the flag -- 11: Church and state. Civil religion--and no religion ; Just leave Christmas alone ; Religion as taste -- Part 3. Politics, foreign and domestic. 12: The two last tribes of Israel. The miracle, at 60 ; The Holocaust and Jewish identity ; Demystifying Judaism ; How to fight academic bigotry ; Do we really mean "Never again"? -- 13: Keeping the world at bay. How to deal with countries gone mad ; The Iranian "moderate" ; Middle East peace and the great Muslim civil war ; The Bush legacy ; Iraq, abandoned ; The climate pact swindle ; Russia rising ; To die for Estonia? ; Trump and the "Madman Theory" -- 14: Democracy and its discontents. In defense of fanatics ; The death penalty and the Constitution ; Finally getting it right on affirmative action ; The right-to-work dilemma ; Brexit: sovereign kingdom or Little England? ; Trump derangement syndrome: you can't govern by id ; Revolt of the attorneys general ; American democracy: not so decadent after all -- 15: On liberty. Constitutions, conservatism and the genius of the Founders ; The meaning of human rights -- Part 4. Competing visions: America's role and the course of world history. 16: Reluctant colossus. When to intervene ; The arrow of history ; Trump's foreign policy revolution -- 17: The end of "the end of history". After a mere 25 years, the triumph of the West is over ; The coming disillusionment of liberated Europe ; The authoritarian temptation -- Part 5. Speaking in the first person. 18: A life without regrets. An anniversary of sorts ; Choosing a life ; A statement of principle ; Beauty and soul ; A note to readers ; Eulogy / by Daniel Krauthammer
Includes bibliographical references and index
Keywords: Krauthammer, Charles, -- 1950-2018.; Popular culture -- United States -- History; Popular culture -- History -- United States; United States -- Politics and government; United States -- Civilization; Essays; History